Method for preparing sub-10nm iron oxide composite material through 3D printing and application of sub-10nm iron oxide composite material

Through the combination of solvent-thermal method and 3D printing technology, iron oxide composite materials with stable structure and uniform particle size were prepared, which solved the problems of particle size control and structure customization in traditional methods, achieved efficient catalytic, magnetic and energy storage performance, and was environmentally friendly and low-cost.

CN119875276AActive Publication Date: 2025-04-25NANJING SHANGSHAN ENVIRONMENTAL ENG TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411961448.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-25
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

Traditional iron oxide nanomaterial preparation methods are difficult to effectively control particle size, prevent agglomeration and achieve structural customization, which affects its catalytic, magnetic properties, and has the risk of high energy consumption and pollution.

Method used

Sub-10 nm iron oxide nanoparticles were synthesized by solvothermal method and evenly dispersed in polymer matrix. The iron oxide composite material with stable structure and uniform particle size was prepared by 3D printing technology.

Benefits of technology

The high specific surface area, good dispersion and customizable structure of iron oxide composite materials have been achieved, which significantly improves its performance in environmental catalysis, magnetic separation and energy storage. It has a low-cost process, environmentally friendly and non-toxic, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a method for preparing a sub-10nm iron oxide composite material through 3D printing and application, sub-10nm iron oxide nanoparticles are synthesized through a solvothermal method and are uniformly dispersed in a polymer substrate material such as acrylic resin, and then the mixed material is shaped by using a 3D printing technology. And the iron oxide composite material with stable structure and uniform particle size is obtained by regulating and controlling printing conditions and a post-treatment process. The composite material has a high specific surface area, good dispersibility and a customizable structure, and the performance of the composite material in the aspects of environmental catalysis, magnetic separation, energy storage and the like is remarkably improved. The method provided by the invention has the characteristics of strong operability, low cost, environmental protection, no toxicity and the like, is suitable for large-scale production, and promotes wide application of the iron oxide nano material in multiple fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nanomaterial preparation and additive manufacturing, and in particular to a method for preparing a sub-10 nm iron oxide composite material by 3D printing and its application. Background Art

[0002] Iron oxide nanomaterials have attracted widespread attention due to their unique properties in catalysis, energy, environmental remediation, medical imaging and sensing, especially iron oxide nanoparticles with a particle size of less than 10 nm. They have a high specific surface area, abundant active sites and quantum size effects, which can significantly improve the performance of materials in these applications. However, traditional preparation methods such as chemical precipitation, solvothermal method, thermal decomposition, etc. have significant technical bottlenecks in controlling the particle size of iron oxide, achieving structural customization and preventing agglomeration. Due to the large surface energy of iron oxide nanoparticles, they are easy to agglomerate to form aggregates, resulting in a reduction in specific surface area and active sites, affecting their catalytic, magnetic and other properties. Even if surfactants are added during the preparation process to reduce agglomeration, impurities may still be introduced, affecting the purity and electrochemical properties of the material.

[0003] Traditional preparation methods also have limitations in the customization of the macroscopic structure of iron oxide materials, making it difficult to meet application requirements in complex environments. For example, in the field of photocatalysis, iron oxide materials need to be made into porous structures or specific shapes to improve light absorption and catalytic efficiency; in biomedical imaging, iron oxide materials need to be compounded onto specific carriers to achieve targeted delivery. In addition, the stability and regeneration of iron oxide nanomaterials in applications such as catalysis and energy storage are also particularly critical to the practical application of the materials. Iron oxide materials may be oxidized or inactivated under repeated use and in environments such as high temperature and high humidity, thereby reducing their performance. Therefore, improving the durability of the material and maintaining stable active sites have become urgent problems to be solved.

[0004] As an emerging additive manufacturing technology, 3D printing has unique advantages in structural design, manufacturing customization and material utilization, and provides a new method for the preparation and structural control of iron oxide nanomaterials. 3D printing can not only achieve precise control of the macroscopic morphology, but also accurately adjust the microstructure of the material through printing parameters. For example, 3D printing combines iron oxide nanomaterials with polymer matrices to form composite materials, which not only prevents the agglomeration of nanoparticles, but also improves the uniform distribution of particles within the material. Through 3D printing, the unique properties of iron oxide nanomaterials can be combined with structural advantages to achieve size control, distribution optimization and structural stability, making their application in multiple fields more feasible.

[0005] In addition, the traditional nanomaterial preparation process usually involves toxic chemicals, high temperature and high pressure, and complex post-processing steps, which have high costs and potential environmental risks. With the improvement of environmental awareness, low-energy consumption, low-pollution and cost-effective preparation processes have become increasingly important. 3D printing technology not only simplifies the preparation process of iron oxide composites, but also reduces the use of harmful solvents, which meets the needs of sustainable development. Therefore, the construction of sub-10 nm iron oxide composites with stable structure and uniform distribution through 3D printing technology will effectively solve the technical difficulties of traditional methods in particle size control, agglomeration problems and structural customization, and promote the wide application of this material in environmental catalysis, energy storage and biomedicine. Summary of the invention

[0006] The purpose of the present invention is to provide a method and application for preparing a sub-10 nm iron oxide composite material by 3D printing, which overcomes the shortcomings of traditional preparation technology in terms of particle size control, agglomeration stability and macroscopic structure customization. Through the preparation method of the present invention, a sub-10 nm iron oxide composite material with high specific surface area, good dispersibility and customizable structure can be obtained, thereby significantly improving its performance in environmental catalysis, magnetic separation and energy storage.

[0007] The preparation method of the present invention first synthesizes sub-10 nm iron oxide nanoparticles by a solvent thermal method, then evenly disperses them in a polymer base material such as an acrylic resin, and uses a 3D printing device to shape the mixed material. By adjusting the printing conditions and post-processing process, an iron oxide composite material with a stable structure and uniform particle size is finally obtained, and the material exhibits excellent catalytic, magnetic and conductive properties. The method has the characteristics of strong operability, low cost, environmental protection and non-toxicity, and is suitable for large-scale production.

[0008] The technical solution adopted by the present invention to achieve the above-mentioned purpose is as follows: A method for preparing a sub-10 nm iron oxide composite material by 3D printing, comprising the following steps: Step (1) Preparation of iron oxide nanoparticles: dissolving ferric nitrate in ethylene glycol solution to prepare a solution with a concentration of 0.5 to 1.25 M, transferring the solution to a high-pressure reactor, reacting at a temperature of 105° C. to 115° C. for 3 to 5 hours, cooling to room temperature, removing impurities by repeated washing with deionized water and ethanol, and then centrifuging, and finally drying the separated nanoparticles to obtain iron oxide nanoparticles with a particle size of 5 to 10 nm; Step (2) Preparation of nanoparticle dispersion: dispersing the iron oxide nanoparticles obtained in step a) in an acrylic resin solution, wherein the solid content of the acrylic resin solution is controlled within a range of 10% to 30%, and adding a surfactant accounting for 1% to 10% of the mass of the iron oxide nanoparticles, and ensuring that the nanoparticles are evenly distributed in the resin solution by stirring and ultrasonic dispersion treatment to form a dispersion; Step (3) 3D printing: The dispersion prepared in step b) is loaded into a 3D printing device, and 3D printing is performed by adjusting printing parameters. After printing, drying and heat treatment are performed to obtain an iron oxide composite material with a stable structure and uniform particle size.

[0009] The present invention provides a method and application for preparing a sub-10 nm iron oxide composite material by 3D printing, which has the following obvious advantages over the existing process: 1. Precise control of nanostructure and macroscopic morphology of materials: Through the combination of solvothermal method and 3D printing technology, the particle size and distribution of iron oxide particles can be controlled at the nanoscale. At the same time, the macroscopic shape of the material can be precisely controlled through 3D printing technology, which is suitable for the construction of a variety of complex structures.

[0010] 2. Efficient physical and chemical properties: The composite material of the present invention has a high specific surface area, good electronic conductivity and chemical stability, which is conducive to achieving excellent performance in photocatalytic degradation and electrochemical energy storage applications. Experiments show that the photocatalytic degradation rate of the material under visible light irradiation exceeds 95%, and it exhibits excellent cycle stability in lithium battery applications.

[0011] 3. Green, environmentally friendly and low cost: The raw materials used in the present invention are non-toxic and environmentally friendly, the preparation process is simple, and no high temperature or highly toxic chemicals are required, which meets the requirements of green manufacturing. The 3D printing preparation process has the characteristics of low energy consumption and low cost, is suitable for large-scale production, and meets the needs of industrial applications.

[0012] 4. Wide application potential: The 3D printed iron oxide composite material of the present invention is suitable for a variety of applications, including photocatalytic degradation of water pollutants, magnetic separation, lithium battery negative electrode materials and supercapacitors, etc. It shows good performance and potential market in wastewater treatment, air purification and clean energy applications.

[0013] 5. Excellent reusability: The material maintains high stability during multiple uses and regeneration, and can still maintain more than 90% of its catalytic performance after repeated use, greatly reducing the cost of use. The good dispersibility and stability of iron oxide nanoparticles make the composite material perform well in efficient degradation and separation applications. DETAILED DESCRIPTION

[0014] The technical solution of the present invention is described in detail below in conjunction with embodiments: A method for preparing a sub-10 nm iron oxide composite material by 3D printing, comprising the following steps: Step (1) Preparation of iron oxide nanoparticles: Dissolve iron nitrate (Fe(NO3)3·9H2O) in ethylene glycol solution to prepare a solution with a concentration between 0.5 and 1.25 M, preferably in the range of 0.75 to 1.0 M. Subsequently, transfer the solution to a high-pressure reactor and react at a temperature of 105°C to 115°C for 3 to 5 hours to ensure uniform growth of the iron oxide nanoparticles. After the reaction, cool the solution to room temperature, remove impurities by repeated washing with deionized water and ethanol, and centrifuge at a speed of 8000 to 12000 rpm, preferably 10000 rpm. Finally, dry the separated nanoparticles to obtain iron oxide nanoparticles with a particle size of 5 to 10 nm.

[0015] Step (2) Preparation of nanoparticle dispersion: The iron oxide nanoparticles prepared above are dispersed in an acrylic resin solution, wherein the solid content of the acrylic resin solution is controlled within a range of 10% to 30%. At the same time, a surfactant (such as polyethylene glycol (PEG) or polyvinyl pyrrolidone (PVP)) is added at 1% to 10%, preferably 3% to 5%, of the mass of the iron oxide nanoparticles to improve the dispersibility of the nanoparticles in the resin solution. The nanoparticles are uniformly distributed in the resin solution by sufficient stirring and ultrasonic dispersion treatment for 30 to 60 minutes, preferably 40 to 50 minutes, to form a stable dispersion.

[0016] Step (3) 3D printing: The prepared dispersion is loaded into a light-curing 3D printing device, and high-precision and high-efficiency 3D printing is achieved by precisely controlling the parameters of the printing device, such as exposure time (1 to 10 seconds), layer thickness (0.01 to 0.1 mm), and scanning speed. After printing, the composite material is placed in a vacuum drying oven and dried at a temperature of 50°C to 80°C for 2 to 24 hours to remove residual solvent. Subsequently, heat treatment is performed, with the temperature controlled between 100°C and 130°C, preferably 110°C to 120°C, for no more than 2 hours to further improve the mechanical and thermal stability of the material.

[0017] An application of preparing a sub-10 nm iron oxide composite material by 3D printing, wherein the composite material has a high specific surface area, good dispersibility and a customizable structure, and is suitable for environmental catalysis, magnetic separation, energy storage, biomedicine and other fields. Example

[0018] A method for preparing a sub-10 nm iron oxide composite material by 3D printing, comprising the following steps: Step (1) Preparation of iron oxide nanoparticles: Accurately weigh 15.21 g of iron nitrate (Fe(NO3)3·9H2O) and dissolve it in 100 ml of ethylene glycol to prepare a solution with an accurate concentration of 1.0 M. The solution was sealed and transferred to an autoclave, and reacted at a strictly controlled temperature of 110±1°C for 4 hours. After the reaction was completed, it was quickly cooled, washed repeatedly with deionized water and ethanol for 3 times, and centrifuged at 10,000 rpm for 15 minutes to finally obtain iron oxide nanoparticles with a uniform particle size of about 7 nm.

[0019] Step (2) Preparation of dispersion: The above nanoparticles were dispersed in 200 mL of an acrylic resin solution containing 20% ​​solid content, and polyethylene glycol (PEG-4000) was added as a surfactant at a concentration of 5% by weight of the nanoparticles. The mixture was stirred with a magnetic stirrer for 30 minutes, and then subjected to ultrasonic dispersion treatment for 45 minutes to ensure that the particles were evenly dispersed.

[0020] Step (3) 3D printing: The dispersion was loaded into a high-precision light-curing 3D printing device, and the exposure time was set to 5 seconds, the layer thickness was 0.05 mm, and the scanning speed was 20 mm / s. After printing, vacuum drying was performed at 60±5°C for 12 hours, followed by heat treatment at 120±5°C for 1 hour to enhance the mechanical properties of the material.

[0021] The iron oxide composite material prepared by the present invention has a specific surface area of ​​190 m² / g, and the iron oxide particle size is uniformly distributed between 7-9nm, with a small particle size and good uniformity. The porosity of the iron oxide composite material is 0.48 cm³ / g, and the pore size distribution is mainly concentrated in 2-4 nm. The material has a density of 2.25 g / cm³ and exhibits excellent thermal stability at 250°C, with almost negligible mass loss. Comparison example For ease of comparison, data for three groups of control materials are provided. The first group of control materials was prepared by the traditional sol-gel method, with a specific surface area of ​​140 m² / g, an iron oxide particle size of 18-22 nm, a porosity of 0.38 cm³ / g, and a wide pore size distribution, indicating that the structure is relatively loose. The second group of control materials was prepared by a high-temperature solid phase method, with a specific surface area of ​​125 m² / g, an iron oxide particle size of 15-18 nm, and a porosity of 0.40 cm³ / g, and the overall performance was inferior to that of the patented material. The third group of control materials is a commercially available iron oxide composite material with a specific surface area of ​​100 m² / g, an iron oxide particle size of 25-30 nm, and a low porosity of only 0.30 cm³ / g. By comparison, it can be seen that the material of Example 1 of the present invention is significantly superior to the control material in key parameters such as specific surface area, particle size and porosity, showing more superior structural properties. Example

[0022] A method for preparing a sub-10 nm iron oxide composite material by 3D printing, comprising the following steps: Step (1) Preparation of iron oxide nanoparticles: 7.6 g of iron nitrate was dissolved in 100 mL of ethylene glycol to prepare a 0.5 M solution. The solution was reacted at 105 ± 2 °C for 6 hours, and the obtained nanoparticles had a particle size of about 9 nm.

[0023] Step (2) Preparation of dispersion: The nanoparticles were dispersed in an acrylic resin solution containing 15% solid content, and 3% of the weight of the nanoparticles was added with polyvinyl pyrrolidone (PVP K30). The dispersion was subjected to ultrasonic dispersion treatment for 30 minutes while being gently stirred to ensure uniformity.

[0024] Step (3) 3D printing: the printing parameters were adjusted to an exposure time of 3 seconds, a layer thickness of 0.1 mm, and a scanning speed that remained unchanged. The drying and heat treatment conditions were the same as those in Example 1.

[0025] The iron oxide composite material prepared by the present invention has a specific surface area of ​​175 m² / g, an iron oxide particle size of 9-12 nm, a uniform particle size distribution, a porosity of 0.44 cm³ / g, and a pore size mainly concentrated in 3-5 nm, showing an excellent microscopic pore structure and a large surface contact area. The iron oxide composite material has a density of 2.30 g / cm³ and exhibits good thermal stability at 250°C, with a mass loss of no more than 3%. Compared with three groups of control materials: the first group of control materials (prepared by traditional sol-gel method) has a specific surface area of ​​140 m² / g, an iron oxide particle size of 18-22 nm, and a porosity of 0.38 cm³ / g; the second group of control materials (prepared by high-temperature solid phase method) has a specific surface area of ​​125 m² / g, an iron oxide particle size of 15-18 nm, and a porosity of 0.40 cm³ / g; the third group of control materials (commercially available materials) has a specific surface area of ​​100 m² / g, an iron oxide particle size of 25-30 nm, and a porosity of only 0.30 cm³ / g. Compared with the control materials, the material of Example 2 of the present invention has obvious advantages in specific surface area, particle size distribution and pore structure, showing a more compact structure and superior surface properties. Example

[0026] A method for preparing a sub-10 nm iron oxide composite material by 3D printing, comprising the following steps: Step (1) Preparation of iron oxide nanoparticles: 22.8 g of iron nitrate was used to prepare a 1.25 M solution, which was reacted at a wide temperature range of 118-122°C for 3 hours to obtain nanoparticles with a particle size of approximately 6 nm. The purity was ensured by a more rigorous washing and centrifugation process.

[0027] Step (2) Preparation of dispersion: Disperse in a resin solution containing 30% solid content, add PEG-6000 with a mass ratio of 10% of the nanoparticles, and disperse by ultrasonic for 60 minutes, during which time an ice bath is used to keep the dispersion temperature stable.

[0028] Step (3) 3D printing: The exposure time was extended to 10 seconds and the layer thickness was reduced to 0.01 mm to improve printing accuracy. The drying temperature was 80±5°C and the time was extended to 12 hours to ensure thorough drying. The heat treatment was carried out at a wide temperature range of 125-135°C for 1.5 hours to explore the effect of higher temperatures on material properties.

[0029] The iron oxide composite material prepared by the present invention has a specific surface area of ​​160 m² / g, an iron oxide particle size of 10-13 nm, and is evenly distributed. The porosity of the material is 0.40 cm³ / g, and the pore size is concentrated at 4-6 nm. The density of the iron oxide composite material is 2.28g / cm³, and the thermal stability is good at 250°C, and the mass loss is less than 2%. To compare the performance of three groups of control materials: the first group of control materials (prepared by traditional sol-gel method) has a specific surface area of ​​140 m² / g, an iron oxide particle size of 18-22 nm, and a porosity of 0.38 cm³ / g; the second group of control materials (prepared by high temperature solid phase method) has a specific surface area of ​​125 m² / g, an iron oxide particle size of 15-18nm, and a porosity of 0.40 cm³ / g; the third group of control materials (commercially available materials) has a specific surface area of ​​only 100 m² / g, an iron oxide particle size of 25-30 nm, and a porosity of 0.30 cm³ / g. Compared with the above-mentioned control materials, the material of Example 3 of the present invention is superior to the prior art materials in terms of specific surface area, iron oxide particle size and pore distribution, showing more significant structural advantages and being suitable for high-efficiency application scenarios. Example

[0030] A method for preparing a sub-10 nm iron oxide composite material by 3D printing, comprising the following steps: Step (1) Preparation of iron oxide nanoparticles: 12.16 g of ferric nitrate was dissolved in 100 mL of ethylene glycol to prepare a 0.8 M solution, and the solution was reacted at 113-117° C. for 5 hours to obtain nanoparticles with a particle size of about 8 nm.

[0031] Step (2) Preparation of dispersion: Disperse in a resin solution containing 25% solid content, add 5% PVP K90, and disperse by ultrasonic for 40 minutes, while using a magnetic stirrer to assist dispersion.

[0032] Step (3) 3D printing: The printing parameters are exposure time of 7 seconds and layer thickness of 0.06 mm. The drying and heat treatment conditions are the same as those in Example 1, but the steps of X-ray diffraction (XRD) and scanning electron microscopy (SEM) characterization of the dried samples are added to evaluate the structure and morphology of the materials.

[0033] The iron oxide composite material prepared by the present invention has a specific surface area of ​​180 m² / g, an iron oxide particle size of 6-8 nm, a small particle size and uniform distribution, and a more compact structure. The porosity is 0.46 cm³ / g, and the pore size distribution is mainly concentrated in 2-4 nm, indicating that the material has a large surface contact area and an excellent microscopic pore structure. The density of the iron oxide composite material is 2.25 g / cm³, and it has excellent thermal stability at 250°C, and the mass loss does not exceed 1.5%. For ease of comparison, characterization data of three groups of control materials are provided. The first group of control materials was prepared by the traditional sol-gel method, with a specific surface area of ​​140 m² / g, an iron oxide particle size of 18-22 nm, a porosity of 0.38 cm³ / g, and a wide pore size distribution. The second group of control materials was prepared by a high-temperature solid phase method, with a specific surface area of ​​125 m² / g, an iron oxide particle size of 15-18 nm, and a porosity of 0.40 cm³ / g. The third group of control materials is a commercially available iron oxide composite material, which has a specific surface area of ​​100 m² / g, an iron oxide particle size of about 25-30 nm, and a low porosity of only 0.30 cm³ / g. By comparison, it can be seen that the material of the present invention is significantly superior to the control material of the prior art in terms of specific surface area, iron oxide particle size and porosity, and exhibits more superior structural properties. Example

[0034] A method for preparing a sub-10 nm iron oxide composite material by 3D printing, comprising the following steps: Step (1) Preparation of iron oxide nanoparticles: Use ferric nitrate to prepare a 0.75 M solution (the specific mass is accurately calculated based on the concentration), react at 110-114° C. for 4.5 hours to obtain nanoparticles with a particle size of about 5.5 nm.

[0035] Step (2) Preparation of dispersion: Dispersed in a resin solution containing 18% solid content, 4% PEG-2000 was added, and ultrasonic dispersion was performed for 55 minutes, during which nitrogen was purged to prevent oxidation.

[0036] Step (3) 3D printing: The printing parameters were optimized to an exposure time of 6 seconds, a layer thickness of 0.04 mm, and a scanning speed reduced to 15 mm / s to improve the printing quality. The drying and heat treatment conditions were similar to those in Example 1, but a step of testing the magnetic properties of the heat-treated samples was added.

[0037] The iron oxide composite material prepared by the present invention has a specific surface area of ​​175 m² / g, an iron oxide particle size of 7-9 nm, a small and uniformly distributed particle size, and a compact structure. The porosity is 0.44 cm³ / g, and the pore size distribution is concentrated at 3-5 nm, indicating that the material has a high specific surface area and a stable microporous structure. The density of the iron oxide composite material is 2.28 g / cm³, and it exhibits good thermal stability at 250°C, with a mass loss of no more than 2%. For ease of comparison, characterization data of three groups of control materials are provided. The first group of control materials was prepared by the traditional sol-gel method, with a specific surface area of ​​140 m² / g, an iron oxide particle size of 18-22nm, a porosity of 0.38 cm³ / g, and a wide pore size distribution. The second group of control materials was prepared by a high-temperature solid phase method, with a specific surface area of ​​125 m² / g, an iron oxide particle size of 15-18 nm, and a porosity of 0.40 cm³ / g. The third group of control materials is a commercially available iron oxide composite material, which has a specific surface area of ​​100 m² / g, an iron oxide particle size of about 25-30 nm, and a low porosity of only 0.30 cm³ / g. By comparison, it can be seen that the material of the present invention is superior to the control material of the prior art in terms of specific surface area, iron oxide particle size and porosity, showing significant structural advantages. Example

[0038] A method for preparing a sub-10 nm iron oxide composite material by 3D printing, comprising the following steps: Step (1) Preparation of iron oxide nanoparticles: A slightly lower concentration of 0.75 M ferric nitrate solution was used to react at a precisely controlled temperature of 112 ± 0.5 °C for 5 hours to obtain nanoparticles with a particle size of about 7.5 nm and excellent dispersibility.

[0039] Step (2) Preparation of dispersion: The nanoparticles were dispersed in a resin solution containing 18% solid content, 3% PVP K30 was added, and ultrasonic dispersion treatment was performed for 50 minutes while a circulating water cooling system was used to keep the dispersion temperature constant.

[0040] Step (3) 3D printing: The printing parameters were set to an exposure time of 4 seconds, a layer thickness of 0.07 mm, and a moderate scanning speed. The drying condition was 50±2°C, and the time was extended to 24 hours to ensure complete curing. The heat treatment was performed at 100±2°C for 1.5 hours. Finally, the electrical properties of the printed samples were tested to evaluate their potential for application in conductive materials.

[0041] The iron oxide composite material prepared by the present invention has a specific surface area of ​​170 m² / g, an iron oxide particle size of 10-12 nm, a uniform particle size distribution, and a compact structure. The porosity is 0.42 cm³ / g, the pore size distribution is mainly concentrated in 4-6 nm, the density of the iron oxide composite material is 2.30 g / cm³, and it has excellent thermal stability at 250°C, and the mass loss is less than 1.8%. For ease of comparison, characterization data of three groups of control materials are provided. The first group of control materials was prepared by the traditional sol-gel method, with a specific surface area of ​​140 m² / g, an iron oxide particle size of 18-22 nm, a porosity of 0.38 cm³ / g, and a wide pore size distribution. The second group of control materials was prepared by a high-temperature solid phase method, with a specific surface area of ​​125 m² / g, an iron oxide particle size of 15-18 nm, and a porosity of 0.40 cm³ / g. The third group of control materials is a commercially available iron oxide composite material, which has a specific surface area of ​​100 m² / g, an iron oxide particle size of about 25-30 nm, and a low porosity of only 0.30 cm³ / g. By comparison, it can be seen that the material of the present invention is superior to the control material of the prior art in terms of specific surface area, iron oxide particle size and porosity, and exhibits a tighter structure and optimized pore distribution. A method for preparing a sub-10 nm iron oxide composite material by 3D printing and its application, wherein sub-10 nm iron oxide nanoparticles are synthesized by a solvent thermal method, and are evenly dispersed in a polymer base material such as an acrylic resin, and the mixed material is shaped by 3D printing technology. By regulating the printing conditions and post-processing process, an iron oxide composite material with a stable structure and uniform particle size is obtained. The composite material has a high specific surface area, good dispersibility and a customizable structure, which significantly improves its performance in environmental catalysis, magnetic separation and energy storage. The preparation method of the present invention has the characteristics of strong operability, low cost, environmental protection and non-toxicity, is suitable for large-scale production, and promotes the wide application of iron oxide nanomaterials in many fields.

[0042] Those skilled in the art can understand that the above-mentioned embodiments are specific examples for implementing the present application, and in practical applications, various changes can be made to them in form and detail without departing from the spirit and scope of the present application. Any person skilled in the art can make their own changes and modifications without departing from the spirit and scope of the present application, so the scope of protection of the present application shall be based on the scope defined in the claims.

Claims

1. A method for preparing a sub-10 nm iron oxide composite material by 3D printing, characterized in that: The following steps are involved: Step (1) Preparation of iron oxide nanoparticles: dissolving ferric nitrate in ethylene glycol solution to prepare a solution with a concentration of 0.5 to 1.25 M, transferring the solution to a high-pressure reactor, reacting at a temperature of 105° C. to 115° C. for 3 to 5 hours, cooling to room temperature, removing impurities by repeated washing with deionized water and ethanol, and then centrifuging, and finally drying the separated nanoparticles to obtain iron oxide nanoparticles with a particle size of 5 to 10 nm; Step (2) Preparation of nanoparticle dispersion: dispersing the iron oxide nanoparticles obtained in step a) in an acrylic resin solution, wherein the solid content of the acrylic resin solution is controlled within a range of 10% to 30%, and adding a surfactant accounting for 1% to 10% of the mass of the iron oxide nanoparticles, and ensuring that the nanoparticles are evenly distributed in the resin solution by stirring and ultrasonic dispersion treatment to form a dispersion; Step (3) 3D printing: The dispersion prepared in step b) is loaded into a 3D printing device, and 3D printing is performed by adjusting printing parameters. After printing, drying and heat treatment are performed to obtain an iron oxide composite material with a stable structure and uniform particle size.

2. The preparation method according to claim 1, characterized in that: The concentration of the ferric nitrate solution in step a) is 0.75 to 1.0 M, the reaction temperature is 110±1° C., and the reaction time is 4 hours.

3. The preparation method according to claim 1, characterized in that: In step b), the solid content of the acrylic resin solution is 20%, the surfactant is polyethylene glycol or polyvinyl pyrrolidone, the added amount is 3% to 5% of the mass of the iron oxide nanoparticles, and the stirring and ultrasonic dispersion treatment time is 40 to 50 minutes.

4. The preparation method according to claim 1, characterized in that: In step c), the parameters of the 3D printing equipment are set to an exposure time of 1 to 10 seconds, a layer thickness of 0.01 to 0.1 mm, and after printing, drying at a temperature of 50° C. to 80° C. for 2 to 24 hours. The heat treatment temperature is controlled between 100° C. and 130° C. for no more than 2 hours.

5. An application of preparing a sub-10 nm iron oxide composite material by 3D printing, wherein the 10 nm iron oxide composite material is prepared according to the preparation method according to any one of claims 1 to 4, characterized in that: Used in environmental catalysis, magnetic separation, energy storage and biomedicine.

Citation Information

Patent Citations

  • Nanocrystalline iron oxide-based magnetic material for 3D printing and preparing method thereof

    CN104200948A

  • Particle size and shape adjustable magnetic alpha-Fe2O3 nano powder preparation method

    CN108439482A

  • Nano-metal 3D printing ink and application thereof

    WO2022262801A1